Fotossíntese e crescimento de Coffea arabica L. submetido à aplicação de piraclostrobina em diferentes disponibilidades hídricas - Peloso, Anelisa de Figueiredo (2016)
In coffee, water deficiency is the main cause of environmental stress, limiting production. In order to minimize the effects caused by water deficiency, the objective of this study is to investigate some physiological aspects caused by pyraclostrobin in p